Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Show that $$\sum_{n=1}^\infty \frac{z^{2^n}}{1-z^{2^{n+1}}}$$ is algebraic.

More specifically, solve this and get exact values.

Then use the result to evaluate $$\sum_{n=0}^\infty \frac{1}{F_{2^n}}$$ where $$F_n=\frac{\alpha^n-\beta^n}{\alpha-\beta}$$ and $\alpha=\frac{1+\sqrt{5}}{2}$ and $\beta=\frac{1-\sqrt{5}}{2}$.

share|cite|improve this question

Hint: expand each term as a power series in $z$, and notice that the double sum can be rewritten as a single sum.

share|cite|improve this answer
I've expanded the power series in Z, but I'm not sure what you mean by double sum. Excuse my ignorance! – Sean Hurron Feb 3 '12 at 20:12

Robert means this... $$\begin{align} \sum_{n=1}^\infty \frac{z^{2^n}}{1-z^{2^{n+1}}} &= \sum_{n=1}^\infty z^{2^n}\sum_{k=0}^\infty z^{k2^{n+1}} = \sum_{n=1}^\infty \sum_{k=0}^\infty z^{2^n+k2^{n+1}} \\&= \sum_{n=1}^\infty \sum_{k=0}^\infty z^{2^n(1+2k)} = \sum_{m=1}^\infty z^{2m} = \frac{z^2}{1-z^2} \end{align}$$ Can you figure out the reason to go from the "double sum" in $n,k$ to the "single sum" in $m$?

share|cite|improve this answer

There is in fact a nice closed form for the partial-sums that you can find just by calculating a bit:

$$ \begin{align*} f(z) &= \frac{z^2}{1-z^4} + \frac{z^4}{1-z^8} + \frac{z^8}{1-z^{16}} + \dots \\ &= \frac{z^2(1+z^4)+z^4}{1-z^8} + \frac{z^8}{1-z^{16}} +\dots \\ &= \frac{z^2 + z^4 + z^6}{1-z^8} + \frac{z^8}{1-z^{16}} +\dots \\ &= \frac{(z^2 + z^4 + z^6)(1+z^8)+z^8}{1-z^{16}}+ \dots \\ &= \frac{z^2+z^4 + z^6+z^8+z^{10} + z^{12}+z^{14}}{1-z^{16}}+\dots \end{align*} $$

So first few partial sums are given by

$$\begin{align*} f_1(z)&= \frac{z^2}{1-z^4} = \frac{z^2-z^4}{1-z^2}\frac1{1-z^4} \\ f_2(z) &= \frac{z^2+z^4+z^6}{1-z^8} = \frac{z^2-z^8}{1-z^2}\cdot \frac1{1-z^8} \\ f_3(z) &= \dots = \frac{z^2-z^{16}}{1-z^2}\cdot \frac1{1-z^{16}}\end{align*} $$

It should then be easy to show by induction that $$ f_n(z) = \frac{z^2}{1-z^2}\cdot \frac{1-z^{2^{n-1}}}{1-z^{2^n}}. $$ The second factor is $1 + O(z^{2^{n-1}})\to 1$, as $n\to\infty$. thus $$\boxed{f(z) = \displaystyle\lim_{n\to\infty} f_n(z) = \frac{z^2}{1-z^2}}$$

Unfortunately, I can't get WolframAlpha to find possible mistakes, so I hope someone else will.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.